2023
DOI: 10.3390/ijms24076674
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms Involved in Hydrogen Sink in the Gastrointestinal Tract of Chickens

Abstract: Hydrogen sink is a beneficial process, which has never been properly examined in chickens. Therefore, the aim of this study was to assess the quantity and quality of microbiota involved in hydrogen uptake with the use of real-time PCR and metagenome sequencing. Analyses were carried out in 50 free-range chickens, 50 commercial broilers, and 54 experimental chickens isolated from external factors. The median values of acetogens, methanogens, sulfate-reducing bacteria (SRB), and [NiFe]-hydrogenase utilizers meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…With this in mind, Cisek et al aimed to identify the microbial communities involved in the hydrogen sink pathway in chickens in order to evaluate the potential role of dietary manipulation in hydrogen metabolism. This study showed that acetogenesis is the predominant metabolic pathway, and further studies are needed to determine the role of specific gut microbial communities in the hydrogen sink in order to evaluate the impact of dietary manipulation of H 2 production [7].…”
mentioning
confidence: 94%
“…With this in mind, Cisek et al aimed to identify the microbial communities involved in the hydrogen sink pathway in chickens in order to evaluate the potential role of dietary manipulation in hydrogen metabolism. This study showed that acetogenesis is the predominant metabolic pathway, and further studies are needed to determine the role of specific gut microbial communities in the hydrogen sink in order to evaluate the impact of dietary manipulation of H 2 production [7].…”
mentioning
confidence: 94%